2013
DOI: 10.1152/ajpcell.00101.2012
|View full text |Cite
|
Sign up to set email alerts
|

Combined in vivo and in silico investigations of activation of glycolysis in contracting skeletal muscle

Abstract: The hypothesis was tested that the variation of in vivo glycolytic flux with contraction frequency in skeletal muscle can be qualitatively and quantitatively explained by calciumcalmodulin activation of phosphofructokinase (PFK-1). Ischemic rat tibialis anterior muscle was electrically stimulated at frequencies between 0 and 80 Hz to covary the ATP turnover rate and calcium concentration in the tissue. Estimates of in vivo glycolytic rates and cellular free energetic states were derived from dynamic changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
(107 reference statements)
0
19
0
Order By: Relevance
“…Similarly, F2,6bP regulation would constitute a major switch between glycolytic and gluconeogenetic modes of metabolism. This may fit with the apparent small dynamic range noted for F2,6bP in mammalian skeletal muscle , which does not perform gluconeogenesis. Again, manipulation of this system in yeast did not seem to have a profound effect on flux in either direction, even when FBPase was overexpressed in the absence of F2,6bP .…”
Section: Bioenergetics: How Is the Atp Generating Activity Of Glycolymentioning
confidence: 58%
“…Similarly, F2,6bP regulation would constitute a major switch between glycolytic and gluconeogenetic modes of metabolism. This may fit with the apparent small dynamic range noted for F2,6bP in mammalian skeletal muscle , which does not perform gluconeogenesis. Again, manipulation of this system in yeast did not seem to have a profound effect on flux in either direction, even when FBPase was overexpressed in the absence of F2,6bP .…”
Section: Bioenergetics: How Is the Atp Generating Activity Of Glycolymentioning
confidence: 58%
“…There are several cell types for which aerobic glycolysis is well documented. For instance, endothelial cells get about 85% of their energy from glycolytic ATP (Ghesquiere et al, 2014); fast-twitch muscle fibers get most energy from glycolysis (Schmitz et al, 2013); activated microglia utilize glycolytic ATP (Voloboueva et al, 2013); and finally, in humans it has been convincingly shown that during brain activation by learning-associated tasks there is a significant increase in aerobic glycolysis without a change (or even with a decrease) in oxygen consumption (Madsen et al, 1995;Shannon et al, 2016). Regarding glucose metabolism, this scenario suggests the existence of two ATP generators in a cell: glycolytic provides rapid energy during acute energy demands, presumably mostly for the membrane-associated processes such as K 1 /Na 1 -ATPase (Fernandez-Moncada and Barros, 2014;Glitsch and Tappe, 1993;Silver and Erecinska, 1997) and Ca 21 -ATPase (Kahlert and Reiser, 2000;Xu et al, 1995), while mitochondria-produced ATP supports all basal/homeostatic cellular energy needs (Epstein et al, 2014).…”
Section: Short Outline Of Main Glucose Functionsmentioning
confidence: 99%
“…Fast-twitch fibres are predominant in muscles capable of short bursts of fast movement and only contain a few mitochondria. These fibres obtain most ATP by glycolysis and increase their glycolytic rate at heavy exercise [16]. Slow-twitch fibres, in contrast, predominate in muscles contracting slowly and steadily.…”
Section: Introductionmentioning
confidence: 99%